Dermatoglyphics in patients with Cenani-Lenz type syndactyly: Studies in a new case - (:unkn) unknown (WILEY-LISS, 1997)
We describe an additional case of Cenani-Lenz syndactylism in a 41/2-year-old boy from a consanguineous Turkish family. The digital anomalies consisted partly of synostosis and partly of malformations of the phalanges. Although there was no radio-ulnar synostosis or abnormality of the bones of the feet, the findings are comparable to those described in the Cenani-Lenz type of syndactyly. me analysed the dermatoglyphics of our patient and compared them with those previously reported. We also investigated the relationship between the bony malformations and the dermatoglyphic patterns in our patient and in the literature. Am. J. Med. Genet. 70:341-345, 1997. (C) 1997 Wiley-Liss, Inc.
Keywords: syndactyly; synostosis; oligodactyly; hand malformations; dermatoglyphics